DHEA improves the antioxidant capacity of endometrial stromal cells and improves endometrium receptivity via androgen receptor. (March 2016) - Qin, Aiping; Qin, Jinchun; Jin, Yufu; Xie, Wei; Fan, Li; Jiang, Lingyun; Mo, Fuhua
Abstract: Objective: To investigate the effect of dehydroepiandrosterone (DHEA) on mouse decidual endometrial stromal cells (ESCs) and to explore mechanisms regulating endometrial receptivity. Study Design: Mouse ESCs were incubated with increasing concentrations of DHEA during decidualization. Treatment with flutamide (FLU), a specific androgen receptor (AR) antagonist, was also performed. Flow cytometry was used to measure intracellular reactive oxygen species (ROS). Real time-PCR was used to determine mRNA expression of decidual PRL-related protein (dPRP), AR, and HomeoboxA10 (HOXA10). Protein levels of AR and HOXA10 were measured by western blot. Results: DHEA significantly inhibited ESC proliferation at concentrations ≥1 × 10 −6  M. DHEA treatment reduced intracellular ROS in a dose-dependent manner. Expression of dPRP was minimally affected by DHEA at concentrations of 1 to 100 nM. However, DHEA (100 nM) significantly increased the expression of HOXA10 at both the mRNA and protein levels ( P  < 0.01). Importantly, this DHEA-mediated increase in HOXA10 was attenuated by treatment with FLU. Finally, neither DHEA nor FLU influenced expression of AR mRNA or protein. Conclusion: Low concentration of DHEA improves the antioxidant capacity of decidual ESCs. DHEA treatment may also improve endometrium receptivity via AR.